Clinical practice in European centres treating paediatric posterior fossa tumours with pencil beam scanning proton therapy - Toussaint, Laura; Matysiak, Witold; Alapetite, Claire; Aristu, Javier; Bannink-Gawryszuk, Agata; Bolle, Stephanie; Bolsi, Alessandra; Calvo, Felipe; Cerron Campoo, Fernando; Charlwood, Frances; Demoor-Goldschmidt, Charlotte; Doyen, Jérôme; et al. (Radiotherapy and oncology, 2024)
BACKGROUND AND PURPOSE: As no guidelines for pencil beam scanning (PBS) proton therapy (PT) of paediatric posterior fossa (PF) tumours exist to date, this study investigated planning techniques across European PT centres, with special considerations for brainstem and spinal cord sparing. MATERIALS AND METHODS: A survey and a treatment planning comparison were initiated across nineteen European PBS-PT centres treating paediatric patients. The survey assessed all aspects of the treatment chain, including but not limited to delineations, dose constraints and treatment planning. Each centre planned two PF tumour cases for focal irradiation, according to their own clinical practice but based on common delineations. The prescription dose was 54 Gy(RBE) for Case 1 and 59.4 Gy(RBE) for Case 2. For both cases, planning strategies and relevant dose metrics were compared. RESULTS: Seventeen (89 %) centres answered the survey, and sixteen (80 %) participated in the treatment planning comparison. In the survey, thirteen (68 %) centres reported using the European Particle Therapy Network definition for brainstem delineation. In the treatment planning study, while most centres used three beam directions, their configurations varied widely across centres. Large variations were also seen in brainstem doses, with a brainstem near maximum dose (D2%) ranging from 52.7 Gy(RBE) to 55.7 Gy(RBE) (Case 1), and from 56.8 Gy(RBE) to 60.9 Gy(RBE) (Case 2). CONCLUSION: This study assessed the European PBS-PT planning of paediatric PF tumours. Agreement was achieved in e.g. delineation-practice, while wider variations were observed in planning approach and consequently dose to organs at risk. Collaboration between centres is still ongoing, striving towards common guidelines.
Keywords: Brain Stem; Organs at Risk; Europe; Infratentorial Neoplasms; Radiotherapy Dosage; celková dávka radioterapie; Evropa; mužské pohlaví; protonová terapie; dítě; Child; Child, Preschool; ženské pohlaví; Humans; předškolní dítě; mozkový kmen; plánování radioterapie pomocí počítače; Proton Therapy; infratentoriální nádory; kritické orgány; Female; lidé; Male; Radiotherapy Planning, Computer-Assisted